Factors Related to Depression Level among Malaysian Students Batch 2015-2018 in Universitas Sumatera Utara - Amaiappan, Jesvinder; Eyanoer, Putri Chairani (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Depression is the most common psychological disorder encountered and is a disorder that is mainly characterized by sad and depressed emotional conditions and is associa